PROTEIN REQUIREMENT OF LABEO ROHITA FINGERLINGS BASED ON GROWTH AND AMMONIA EXCRETION - DEBNATH, D.; PAL, A. K.; SAHU, N. P.; YENGKOKPAM, S.; BARUAH, K. (Journal of the Inland Fisheries Society of India, 2021)
A 45-day feeding trial was conducted to study the effect of dietary crude protein levels (viz. 25, 30, 35, 40 or 45% CP) on growth performance and ammonia-N excretion in Labeo rohita fingerlings (av wt 1.07-1.14 g) as a strategy to find quick and effective method for protein requirement determination. The culture system consisted of 20 plastic tanks (5 treatments x 4 replicates) of 100 l capacity, each one of which was stocked with 20 fingerlings. Soyabean meal and fish meal were used as the main protein sources, whereas corn flour and rice polish as major carbohydrate sources for diet formulation. Higher weight gain% (WG%) was recorded in 35, 40 and 45% CP fed groups, but there was no significant variation between these groups. One-slope broken-line regression analysis of WG% exhibited an estimate of 35.37% protein requirement for maximum growth. The pattern of ammonia excretion was similar in different protein fed groups with rapid increase after meal and reaching a maximum at 7-10 h after the meal. Ammonia excretion rate was higher (P<0.05) in fish fed with more protein. But when ammonia-N was expressed as % total N intake, ammonia-N excretion was similar in all the groups fed higher than 25% CP. Broken-line analysis of N excretion (as percentage of N intake) showed highest ammonia-N excretion at an estimated dietary protein level of 33%, which is very close to the protein requirement based on the growth performance of fish. The ammonia excretion rate can serve as a good indicator of the dietary protein requirement, and it is quicker than the growth study. Key words: Labeo rohita, protein requirement, ammonia excretion